Faktor Intrinsik dan Ekstrinsik yang Mempengaruhi Kinerja Guru - Chandra S. Haratua; Muslim Hanief; Asep Nurdin Toha; Ludi Muhamad Nur Mauludin; Muhamad Ikhsan (Attractive : Innovative Education Journal, 2024)
Teachers serve as the frontline agents who play a vital role in the educational process. They are expected to provide high-quality and effective learning experiences for students. Teacher performance is a measure of a teacher's success in carrying out their teaching duties in accordance with their responsibilities and authority. This includes the teacher's ability to plan, implement, and evaluate the learning process, as well as to guide students. There are two categories of factors that influence teacher performance: intrinsic factors and extrinsic factors. Intrinsic factors originate from within the teacher, while extrinsic factors come from the surrounding environment. This research aims to identify and understand the factors from both categories as inputs for schools to improve overall teacher performance. The study employs a qualitative approach using the literature review method, which involves examining various sources to understand the theories and concepts related to the topic being researched. The findings indicate that intrinsic factors such as work discipline, professionalism, self-motivation, competence, and teaching experience are essential foundations for fostering a teacher's dedication and performance. Additionally, extrinsic factors including school leadership, a positive work culture, supportive working conditions, adequate compensation or benefits, school culture, and teacher certification programs play a crucial role in creating a conducive environment for teachers to develop and reach their maximum potential. The synergy between these two sets of factors creates a positive cycle that significantly impacts educational success.